Exploring the Mediating Role of Digital Supply Chain in the relationship Between Green Promotion and Sustainable Small Business Performance Among Indonesian MSMEs - Rahim, Yolanda; Istimaroh (Journal of Social Transformation and Regional Development, 2026)
The increasing demand for environmentally sustainable business practices has encouraged MSMEs to adopt green pricing strategies and digital transformation initiatives. However, the mechanism through which green pricing contributes to sustainable business performance remains insufficiently understood, particularly in developing economies. This study examines the effect of green price on sustainable small business performance and investigates the mediating role of the digital supply chain among MSMEs in East Kalimantan, Indonesia. A quantitative approach was employed using survey data collected from 306 MSME owners and managers. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart-PLS 4.0. The findings reveal that green price does not have a significant direct effect on sustainable small business performance. However, green price significantly influences the adoption of digital supply chain practices, which in turn positively affect sustainable business performance. The results further demonstrate that the digital supply chain fully mediates the relationship between green price and sustainable small business performance. These findings suggest that green pricing strategies alone are insufficient to enhance sustainability outcomes unless supported by digital supply chain capabilities. This study contributes to the sustainability and MSME literature by highlighting the critical role of digital supply chain transformation in converting environmentally oriented pricing strategies into sustainable business performance.